2019
DOI: 10.1080/02699931.2019.1590317
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between gamma-band activity and maths anxiety

Abstract: Previous research has outlined high anxiety in connection with gamma modulation, identifying that gamma-band activity (40-100 Hz) correlates with processing of threat perception, attention and anxiety. Maths anxiety research has also noted the involvement of these aspects, yet this has not been investigated from a neurophysiological standpoint. Electroencephalography (EEG) was used to research gamma-band activity in relation to maths anxiety over two studies.The first measured gamma differences during the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In rodents, changes in slow hippocampal gamma rhythms are generally associated, among other things, with slower running speed or increase in synchronization between CA3 and the cingulate cortex during immobility (Ahmed and Mehta, 2012;Buzsáki, 1986;Buzsáki and Wang, 2012;Zheng et al, 2015). Other studies showed that alteration gamma with anxiety behaviors (Batashvili et al, 2019;Cruces-Solis et al, 2019;Zhou et al, 2018). Nevertheless, to our knowledge, there is no study showing a systematic effect of aging on magnitude of gamma power, except when degeneration is present (Etter et al, 2019;Goutagny et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…In rodents, changes in slow hippocampal gamma rhythms are generally associated, among other things, with slower running speed or increase in synchronization between CA3 and the cingulate cortex during immobility (Ahmed and Mehta, 2012;Buzsáki, 1986;Buzsáki and Wang, 2012;Zheng et al, 2015). Other studies showed that alteration gamma with anxiety behaviors (Batashvili et al, 2019;Cruces-Solis et al, 2019;Zhou et al, 2018). Nevertheless, to our knowledge, there is no study showing a systematic effect of aging on magnitude of gamma power, except when degeneration is present (Etter et al, 2019;Goutagny et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…There are significant differences in network characteristics between HAHV and LAHV, HALV and LALV, and HAHV and HALV in the γ band. In other recent research related to emotion, significant differences were also mainly concentrated in the γ band (Mu et al, 2017;Batashvili et al, 2019). In addition, recent studies on emotion classifiers have found that the γ band provides the highest classification accuracy of any frequency band (Mohammadi et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Data were averaged within a specific segment of the gamma frequency band (35-70 Hz), chosen based on previous research observing gamma activity and threat (30-50Hz; Luo et al, 2009Luo et al, , 2007, anxiety (35-70;Oathes et al, 2008) and math anxiety (35-70;Batashvili et al, 2019).…”
Section: Eeg Recording and Analysismentioning
confidence: 99%
“…Previous research has shown that the gamma band is responsible for the processing of threat-related stimuli (Garcia-Garcia et al, 2010;Maratos et al, 2012) and attentional bias in high anxious individuals (Bar-Haim et al, 2007). This has since been related to math anxiety, whereby high anxious individuals have been shown to display increased gamma power for math-related problems of varying complexities, but not for word-based tasks (Batashvili, Staples, Baker, & Sheffield, 2019). Furthermore, studies have shown that task demand may not be responsible for these increasing effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation